A comunicação de edtechs de educação corporativa: consumo de discursos publicitários sobre o “saber ser” do trabalhador - Silva , Vivian Peres Ribeiro da (2024)
Technology, the increase of connections, and the new relations with knowledge have substantially transformed the world of labour, creating needs for improvement and continuous learning. In response to this demand, a new market of education-based technology startups, known as edtechs, has developed (Williamson, 2015, 2016, 2021, 2022). As part of the platform phenomenon, these companies employ production logics and consumption dynamics that treat intelligence and success as signs of prestige (Canclini, 1997). This research aims to reflect on how these companies are structured in the Brazilian market, especially from the perspective of the symbolic construction of the postmodern worker. To this end, we focus on the market segment of companies offering technological solutions for training and development (T&D) with an emphasis on the development of soft skills, what Pierre Lévy (2010) calls "knowing how to be." We will start by mapping the consumer journey to subsequently analyze advertising materials. For this purpose, we will use a protocol that incorporates the support of theorists from the French discourse analysis tradition, critical discourse analysis, and rhetorical analysis. Among the authors utilized are Dominique Maingueneau (2020), Eni Orlandi (2012, 2022), José Luiz Fiorin (2004), Michel Foucault (2014, 2021), José Luiz Aidar Prado (2013, 2010), Teun Van Dijk (2020) and João Anzanello Carrascoza (2004, 2015).